The economics of innovation - Lambertini, Luca; Cellini, Roberto (Emerald, 2008)
The book is a collection of original research papers by a number of industrial organization economists active in the field of Research and Development theory and policy. The contributions gathered here cover several relevant topics in this area; namely patent policy, the effects of market structure and the internal organization of the firm on R&D incentives and technical progress, R&D cooperation and technological spillovers, innovation and the entry process. Comprehensive views of the acquired knowledge of these topics are presented together with new insights on these issues, including policy insights wherever appropriate. The book is intended for professional researchers in industrial organization, antitrust officers, plus graduate students (at both Master and PhD level).
Includes index.
Keywords: Research and development projects.; elektronické knihy; electronic books